The effects of coordination trainings on different surfaces on the slalom downhill speed velocity of snowboarders - Tanyeri, L.; Öncen, S. (Journal of Education and Training Studies, 2019)
Purpose: Snowboarding is a branch of sport, an individual Alpine sport, which requires superior physical structure. In snowboarding, snowboarders are expected to have high level aerobic and anaerobic strength to become successful. In the present study, the effects of training programs on different surfaces on slalom downhill speed of snowboarding-Alpine snowboarders were examined.